Method for improving performance of seaweed-based straw and prepared seaweed-based straw additionally provided with zein coating
By soaking a seaweed-based straw in zein solution to form a coating, the problem of insufficient swelling and mechanical strength of the seaweed-based straw is solved, and the water resistance and mechanical properties of the straw are improved.
Patent Information
- Application Number
- CN202411556183.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
AI Technical Summary
The existing seaweed-based straws have insufficient performance in swelling resistance and mechanical strength, which limits their popularity in practical applications.
The reaction is carried out by soaking a seaweed-based straw in zein solution to form a stable zein coating, which improves the water resistance and mechanical properties of the straw.
It has achieved significant improvement in the water resistance and mechanical properties of seaweed-based straws, providing better comprehensive performance.
Smart Images

Figure CN119410011A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biological coatings, and in particular relates to a method for improving the performance of seaweed-based straws and a seaweed-based straw coated with zein prepared by the method. Background Art
[0002] In order to cope with the adverse effects of petroleum-based plastic straws on human health and the environment, people have developed biodegradable alternatives such as paper straws and polylactic acid (PLA) straws, which have replaced traditional plastic straws to a certain extent. However, in actual use and commercial promotion, these alternatives have also exposed some defects. For example, paper straws are prone to disintegration during use due to their water resistance, especially in hot water, which affects the consumer experience and sometimes even makes people feel like chewing paper. Although polylactic acid (PLA) straws can be degraded under composting conditions, they will not decompose on their own in the natural environment. The decomposition process requires specific conditions such as temperature, humidity, pH value and specific microorganisms, which significantly increases the processing cost. Therefore, it is not accurate to regard them as completely degradable materials. In addition, the polylactic acid straws currently on the market are mostly made of starch. Under special circumstances, this may have a certain impact on food supply and may even potentially cause food security issues.
[0003] In response to the above problems, the prior art (CN 114311721 A) proposes an innovative solution. This technology focuses on the use of polymers from non-food sources such as seaweed, and develops a new method for preparing straws. The seaweed-based straws prepared by this method can be quickly degraded in the natural environment without the need for composting, while maintaining good water stability. However, due to the inherent water resistance of alginate polymers, seaweed-based straws are insufficient in terms of anti-swelling properties and mechanical strength, which limits their popularity in practical applications. Therefore, further improvements are needed to improve the physical properties of seaweed-based straws to meet new market demands. Summary of the invention
[0004] The present invention provides a method for improving the performance of seaweed-based straws, comprising the following steps:
[0005] The seaweed-based straws are immersed in a zein solution for reaction. After the reaction is completed, the straws are taken out, washed, and dried to obtain seaweed-based straws with improved performance and zein coating.
[0006] In the above method, the reaction time is selected from 1 to 3 hours, preferably 2 hours.
[0007] In the above method, the zein solution is an alcohol aqueous solution of zein; the concentration of the zein solution is selected from 1 to 6%, preferably 2%.
[0008] In the above method, the alcohol aqueous solution is composed of ethanol and water, and the volume ratio is selected from 7 to 9:1 to 3, preferably 7:3.
[0009] In the above method, the pH of the zein solution is selected from 2 to 8, preferably 4.
[0010] The invention provides a seaweed-based straw with a zein coating prepared by the method.
[0011] In the present invention, the seaweed-based straw is prepared by the following method:
[0012] (1) Preparation of gel mold
[0013] Dissolving agar powder and calcium chloride powder in water, stirring and heating; then, pouring the agar solution into a tube mold; solidifying to form a sol-gel transition, and obtaining a gel mold;
[0014] (2) Cross-linking and demolding
[0015] Dissolve sodium alginate powder in water to form a sodium alginate solution; then, immerse the gel mold in the sodium alginate solution for directional diffusion cross-linking; after the cross-linking is completed, take out the gel mold to obtain a hollow tube; immerse the hollow tube in a calcium chloride solution; then, immerse the hollow tube in water to remove excess calcium chloride to obtain a cross-linked and strengthened hollow tube; dry the hollow tube to obtain a seaweed-based straw.
[0016] In the above-mentioned method for preparing seaweed-based straws, in the step (1), the mass ratio of agar powder, calcium chloride powder and water is selected from 0.5 to 10:1 to 30:100; preferably 3:8:100.
[0017] In the method for preparing the seaweed-based straws, in step (1), the temperature is heated to 85-100°C, preferably 95°C.
[0018] In the above-mentioned method for preparing seaweed-based straws, in the step (1), the curing conditions are selected from: curing at 0 to 50° C. for 5 to 100 min; preferably: curing at room temperature for 30 min.
[0019] In the above-mentioned method for preparing seaweed-based straws, in the step (2), the concentration of the sodium alginate solution is 0.5-15%wt; preferably 2%wt.
[0020] In the above-mentioned method for preparing seaweed-based straws, in the step (2), the immersion time in the sodium alginate solution is 10 to 120 minutes, preferably 30 minutes.
[0021] In the above-mentioned method for preparing seaweed-based straws, in the step (2), the concentration of the calcium chloride solution is selected from 0.1 to 1.5M, preferably 0.25M.
[0022] In the method for preparing the seaweed-based straws, in step (2), the time in the calcium chloride solution is 5 to 120 minutes, preferably 15 minutes.
[0023] In the above-mentioned method for preparing seaweed-based straws, in step (2), the time in water is 5 to 60 minutes, preferably 10 minutes.
[0024] The beneficial effects of the present invention are:
[0025] The present invention combines an antisolvent with an electrostatic assembly method, and by adjusting the pH, zein undergoes a protonation reaction, carries a positive charge, and undergoes electrostatic assembly with the charged alginate on the surface of the straw, thereby achieving a stable interface bond and allowing the zein coating to be added to the surface of the straw. Due to the hydrophobicity of zein, the straw with the zein coating has excellent water resistance. In addition, the mechanical properties of the seaweed-based straw after the coating are also greatly improved.
[0026] Zein is a hydrophobic protein extracted from corn. The molecules are connected by disulfide bonds and hydrophobic bonds. It has unique self-assembly characteristics, film-forming properties and water resistance. It can be self-assembled on the surface of the straw through anti-solvents, and can also be electrostatically assembled with alginate. First, solvent exchange causes the phase separation of the zein to occur and deposit on the surface of the straw; then the positively charged zein electrostatically assembles with the alginate straw to achieve a stable combination of the zein coating. Compared with commercial degradable straws and seaweed-based straws, seaweed-based straws with zein coating have better overall performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The effect of pH on the Zeta potential of sodium alginate and zein;
[0028] Figure 2 CLSM images of the coating formed by 2% zein at different pH values;
[0029] Figure 3 CLSM images of coatings formed with different concentrations of zein;
[0030] Figure 4 SEM images of coatings formed with different concentrations of zein;
[0031] Figure 5 The swelling degree of seaweed-based straws coated with prolamin;
[0032] Figure 6 The contact angle of the seaweed-based straw with prolamin coating;
[0033] Figure 7 The bending stress of the seaweed-based straws with prolamin coating;
[0034] Figure 8 Infrared spectra of sodium alginate, zein, and zein-coated algae-based straws;
[0035] Fig. 9 Comparison of the residual rates of various straws at different degradation times;
[0036] Fig.10 The swelling degree (a) and bending stress (b) of each straw at room temperature under different pH levels, as well as the swelling degree (c) and bending stress (d) of each straw in water at different temperatures. DETAILED DESCRIPTION
[0037] In the present invention, the seaweed-based straw is prepared by the following method:
[0038] (1) Preparation of gel mold
[0039] Dissolve 3g agar powder and 8g anhydrous calcium chloride powder in 100g distilled water and heat to 95°C while stirring. Then, immediately pour the agar solution into a tube mold with an inner diameter of 8mm. Curing at room temperature for 30min forms a sol-gel transition and obtains a gel mold (solid).
[0040] (2) Cross-linking and demolding
[0041] Sodium alginate powder was dissolved in deionized water to form a 2% wt sodium alginate solution. The solution was heated at 55°C and stirred vigorously until completely dissolved, then centrifuged for degassing (4000 r min -1, 10min) to obtain a uniform and bubble-free sodium alginate solution. Then, immerse the prepared gel mold in the sodium alginate solution for directional diffusion cross-linking, and the immersion time is 30min. After the cross-linking is completed, take out the gel mold to obtain a hollow tube. The hollow tube is re-immersed in a 0.25M calcium chloride solution to maximize the cross-linking, and the immersion time is 15min. Subsequently, it is immersed in deionized water for 10min to remove excess CaCl2 to obtain a cross-linked and strengthened hollow tube. The hollow tube is fixed (sheathed) on a glass rod with a diameter of 8mm for drying, and the drying conditions are 60°C and 80% relative humidity (adjustable). After drying is complete, demoulding is performed. There are many ways to demold the product. For example, a demolding agent can be applied to the glass rod, or the straw and the glass rod can be directly immersed in water for demolding. The taken out tube blank is put on a new glass rod (the diameter of the support column here is smaller than the diameter of the support column in the previous step, because the tube blank has a certain hardness at this time, and the support column does not need to fit tightly to the inner wall of the tube blank), and then continue drying (drying conditions 60°C, 55% relative humidity) to obtain seaweed-based straws.
[0042] The above-mentioned directed diffusion assembly method (DDA method) can successfully produce biodegradable seaweed-based straws using alginate as a model material. However, the inherent hydrophilicity of alginate still significantly affects the overall performance of the straw, including key properties such as anti-swelling and surface hydrophobicity.
[0043] Zein is a hydrophobic protein extracted from corn. The molecules are connected by disulfide bonds and hydrophobic bonds. It has unique self-assembly characteristics, film-forming properties and water resistance, and is widely used in the food industry. Zein is insoluble in water and soluble in 70% ethanol solution. Therefore, zein can be phase-separated on the surface of another hydrophilic substance by the anti-solvent method to form a core-shell structure. In addition, zein contains a large number of polar amino acids, and the proton and deprotonation reactions of polar amino acids can be controlled by adjusting the pH value to change their electronegativity. Therefore, we speculate that zein can be self-assembled on the surface of the straw by anti-solvent and can also be electrostatically assembled with alginate. Based on this, the present invention first promotes the phase separation of zein by solvent exchange and deposits it on the surface of the straw; then the positively charged zein is electrostatically assembled with the alginate straw to achieve a stable combination of the zein coating, thereby further improving the performance of the seaweed-based straw.
[0044] Other materials used in the present invention, if not otherwise stated, can be obtained through commercial channels. Other terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The present invention is further described in detail below in conjunction with specific examples and with reference to data. The following examples are only for illustrating the present invention, and are not intended to limit the scope of the present invention in any way.
[0045] Example 1
[0046] The steps to construct a zein coating on the surface of the seaweed-based straw are as follows:
[0047] A 10 cm seaweed-based straw (hollow tube) was immersed in 100 mL of zein solution for 2 hours, then taken out, washed, and dried to obtain a seaweed-based straw coated with zein.
[0048] This embodiment provides zein solutions of different concentrations and different pH values, which are prepared by the following method:
[0049] Different masses of zein powder were poured into a certain volume of alcohol-water solution (alcohol-water volume ratio was 7:3) and stirred evenly to prepare zein solutions of different concentrations (1%, 2%, 3%). The pH of the zein solutions was adjusted to 2, 3, 4, 5, 6, 7 and 8 respectively by HCl or NaOH.
[0050] 1. Analysis of Zein Coating Structure
[0051] 1. Zeta potential determination
[0052] The potential of sodium alginate and zein in the pH range of 3-8 was measured using nanoparticle size and potentiometric titrator instruments. The specific experimental steps are as follows: First, a 0.1% sodium alginate (SA) solution was prepared by stirring with ultrapure water as the solvent, and then the solution was divided into six portions, and the pH was adjusted to 3, 4, 5, 6, 7 and 8 respectively using 0.5M HCl or 0.5M NaOH. Then, a 0.1% zein (Zein) solution was prepared using 70% ethanol as the solvent, stirred at room temperature for 15 minutes until completely dissolved, and then the Zein solution was also divided into six portions, and the pH was adjusted to the corresponding value using 0.5MHCl or 0.5M NaOH. Finally, the above samples were measured in zeta mode. The ξ-potential was calculated according to the Henry equation, the experimental temperature was 25.0±0.2℃, and each sample was measured more than three times, and the average value was taken as the final result.
[0053] Test results such as Figure 1 As shown:
[0054] ζ-potential is an important indicator reflecting the charge of a substance. Figure 1 It can be seen that the potential of sodium alginate and zein changes with the change of pH. The isoelectric point (IEP) of Zein solution is 6.12. When the pH is less than 6.12, the Zein solution has a positive charge; when the pH is greater than 6.12, it has a negative charge. In addition, the sodium alginate solution always has a negative charge in the pH range of 2 to 8, and its ζ-value is about -60mV. When the product of the ζ-values of the negatively charged sodium alginate and the positively charged Zein reaches the maximum absolute value, the electrostatic attraction between them is the strongest. According to Figure 1 From the data, it can be clearly seen that at pH 4, the electrostatic interaction between sodium alginate and Zein is the strongest.
[0055] 2. Confocal laser scanning
[0056] (1) Different pH conditions
[0057] The samples were embedded in Leica cryosection embedding medium and fixed at -80°C. Then, the samples were cut into 20 μm thick sections using a cryostat at -20°C and placed on slides. The samples were stained with Nile blue (0.1%) in the dark, and the excess dye was rinsed 2-3 times with deionized water after 1 min and covered with a coverslip. The excitation wavelength of the sample was 633 nm, and CLSM images were taken at 10x magnification, 1024×1024 pixels, and 100 Hz frequency. Multiple measurements and selected images were analyzed and processed using Angio Tool software to calculate and quantify the evolution of the zein coating.
[0058] The above samples are seaweed-based straws with added zein, which are prepared under the conditions of zein concentration of 2% and pH values of 2, 3, 4, 5, 6, and 7, respectively.
[0059] Test results such as Figure 2 As shown:
[0060] Laser confocal microscopy (CLSM) can better understand the dynamic changes of protein networks by visualizing the main structures of polysaccharide / protein complexes. As shown in the figure, a clear alcohol-soluble protein coating can be observed at pH 4, a slightly clear alcohol-soluble protein coating can be observed at pH 3 and 5, and no alcohol-soluble protein coating can be observed at pH 2, 6 and 7. Combined with the potential diagram, at pH 4, zein has the largest negative charge, so a clear and continuous alcohol-soluble protein coating can be formed, while at pH 3 and 5, zein carries less negative charge, so a weak alcohol-soluble protein coating is formed. Under other pH environments, zein is not charged, so no coating can be formed. Therefore, we believe that the main binding force for the construction of alcohol-soluble protein coating is electrostatic attraction, and the antisolvent may only drive alcohol-soluble protein solidification, but cannot be effectively fixed on the surface of the straw.
[0061] (2) Different zein concentration conditions
[0062] The above experiment has observed through CLSM images that a uniform coating can be formed at pH 4 using 2% zein, but a uniform and continuous coating cannot be formed at other pH values. However, in addition to pH driving the formation of the coating, the concentration of zein may also affect the formation of the coating. Therefore, the present invention then explores the effect of zein concentration (1%, 2%, 3%) on the formation of the coating.
[0063] Test results such as Figure 3 As shown:
[0064] Zein with a concentration of 2% can form a uniform and continuous coating, while a zein solution with a concentration of 1% only forms an outer surface zein coating, while a zein solution with a concentration of 3% forms a discontinuous and uneven zein coating. This may be related to the driving force provided by the antisolvent. At a concentration of 1%, less zein solidifies due to the antisolvent, and due to the directional diffusion assembly, the number of negative charges provided by the inner surface of the tube is small, so the effective assembly of the coating cannot be achieved. At a concentration of 3%, the concentration of zein is too high, which will cause a large amount of zein to solidify at the moment of the antisolvent, and it will not be possible to achieve uniform electrostatic assembly with alginate, and even cause the coating to fall off.
[0065] 3. Scanning electron microscopy determination
[0066] In order to further verify the above experimental conclusions, SEM was used to observe the microstructure of the straw cross section.
[0067] The results of the test are as follows Figure 4 As shown:
[0068] When the concentration is 1%, there is no coating on the inner surface, and although a coating is formed on the outer surface, the coating is not tightly bonded; when the concentration is 2%, a continuous and stable coating is formed on both the inner and outer surfaces; when the concentration is 3%, the coating is thicker, but the bonding is not stable and it falls off. Combined with the CLSM images, the previous conclusion is fully verified, that is, the anti-solvent driving force provided by low-concentration zein is weak and cannot form a stable coating, while the electrostatic interaction force provided by high-concentration zein is too strong, and the coating formed is thicker, but it is easy to fall off. The 2% concentration of zein can provide an appropriate phase separation driving force to drive the solidification of zein, and the solidified zein is electrostatically attracted and electrostatically assembled with alginate.
[0069] 2. Water resistance of straw
[0070] This experiment studied the water resistance of seaweed-based straws with zein coating (respectively marked as Group C1, Group C2, and Group C3) prepared at pH 4 and zein concentrations of 1%, 2%, and 3%, respectively, to explore the effect of zein coating on the anti-swelling properties, solubility, and surface hydrophobicity of seaweed-based straws.
[0071] 1. Swelling degree
[0072] The sample was cut into squares (2×2 cm), dried at 105°C for 24 h, and its initial dry weight (W1) was determined. Subsequently, the dried sample was soaked in 50 mL of distilled water for 30 min. The film sample was then taken out, dried with filter paper, and weighed (W2). Each sample was tested three times under the same conditions. The swelling degree (SD) (%) value of the membrane was calculated as follows:
[0073]
[0074] The test results are as follows Figure 5 As shown:
[0075] Compared with the uncoated seaweed-based straws (SA group), the swelling of the coated seaweed-based straws decreased significantly, with the C2 group showing the most significant drop of 53%. Compared with the C1 group (1%) and the C3 group (3%), the swelling of the C2 group decreased by 42.1% and 21.1%, respectively.
[0076] 2. Contact angle
[0077] The water contact angle test of the pipette was performed using a contact angle system equipped with an automated charge coupled device and a video capture system. 2 μL of deionized water was deposited on the surface of the pipette and the contact angle was measured.
[0078] The test results are as follows Figure 6 As shown:
[0079] Compared with the control group without coating, the surface contact angle of group C2 increased by 45.2%, indicating that the surface hydrophobicity of the straw was improved. This shows that adding hydrophobic alcohol-soluble protein to the surface of the straw can effectively prevent water intrusion, while groups C1 and C3 cannot effectively prevent water intrusion due to uneven coating and shedding.
[0080] In summary, compared with other groups, group C2 has the best water resistance, including the most hydrophobic surface and the lowest swelling degree and solubility. That is, the antisolvent driving force and electrostatic assembly force provided by group C2 can form the most continuous and uniform coating, thereby improving the water resistance of the straw.
[0081] 3. Mechanical properties of straws
[0082] Bending test:
[0083] The bending resistance of the straws was characterized using a texture meter equipped with a three-point bending probe. During the three-point bending test, the straws were placed on two roller supports and kept at a fixed distance of 50 mm. The sample was placed on two roller supports and subjected to a concentrated load at the center of the sample at a constant test speed of 3 mm / min at room temperature. The bending strength of the hollow tube can be derived from the following formula:
[0084]
[0085] In formula (1), M is the maximum bending moment, γ is the maximum distance from the center of the tube (equal to d / 2), L is the distance between the two points below the specimen, F is the applied force, d is the outer diameter of the straw, and d is the inner diameter of the straw.
[0086] Test results such as Figure 7 As shown:
[0087] After adding the alcohol-soluble protein coating, the mechanical properties of the seaweed-based straws in group C2 were greatly improved, but the degree of mechanical enhancement of the seaweed-based straws in groups C1 and C3 was not high.
[0088] 4. Infrared spectroscopy analysis of straws
[0089] Infrared spectroscopy analysis of seaweed-based straws coated with zein, such as Figure 8 As shown:
[0090] The characteristic absorption peaks of the infrared spectrum of sodium alginate are mainly concentrated in the range of 3500-3200 cm -1 and 1700~1500cm -1 Two areas. 3500-3200cm -1 The absorption peak is mainly caused by the vibration of hydroxyl and amine groups in sodium alginate. 1700~1500cm -1The absorption peaks are caused by the vibration of carboxyl and carboxylate. The infrared characteristic absorption peaks of zein are at 3406cm -1 There is an OH vibration absorption peak at the wave number of 1656cm -1 There is an amide I band -NH bending vibration at 2920 cm -1 There are CH stretching vibration absorption peaks at 2920 and 1599 cm-1 after alginate is coated with alcohol-soluble protein. -1 The unique stretching vibration absorption peak of zein appeared around 3260 cm-1, which showed that zein was successfully coated on the surface of alginate straw. -1 The OH stretching vibration peak at 3270 cm -1 At 1601cm -1 The CO stretching vibration absorption peak at 1589 cm -1 The above results show that zein mainly relies on the electrostatic assembly of amino groups and carboxyl groups of alginate to combine together. In addition, there are also certain hydrophobic interactions.
[0091] 5. Biodegradability of Straws
[0092] The biodegradability of C2 straws, seaweed-based straws, paper straws, and PLA straws was tested as follows:
[0093] The straws were buried in soil samples from the Qingdao Agricultural University campus at a temperature of 20±2°C and a depth of 10 cm. The straws were regularly extracted and cleaned, and their weight loss rates were measured to evaluate degradation parameters.
[0094] Test results such as Fig. 9 As shown:
[0095] From a structural point of view, after the alcohol-soluble protein coating is added, the overall structure of the straw becomes stronger and denser, which is not conducive to natural degradation and may slow down the natural degradation rate. However, from actual tests, it can be seen that compared with the control group, the seaweed-based straws with the alcohol-soluble protein coating degrade faster and can be completely degraded within 90 days. The degradation rate even exceeds that of paper straws. The reason may be that the main components of seaweed-based straws and paper straws are polysaccharides, while after the alcohol-soluble protein coating is added, the main components of the straws become polysaccharides and proteins, which can provide more and more balanced nutrients for microorganisms, which is conducive to the growth of microorganisms and thus accelerates the degradation rate. From the perspective of degradation rate, straws with alcohol-soluble protein coating degrade faster in the natural environment, thereby avoiding pollution caused by the accumulation of materials in the environment.
[0096] 6. Application in different beverage systems
[0097] To further explore the applicability of seaweed-based straws with zein coating, the anti-swelling properties and wet strength of the straws were evaluated in simulated beverage systems at different pH and temperature.
[0098] Test results such as Fig.10 As shown:
[0099] Seaweed-based straws exhibit excellent anti-swelling properties and wet strength at different pH and temperatures. In addition, compared with seaweed-based straws without alcohol-soluble protein coating, seaweed-based straws with coating exhibit smaller performance fluctuations in different environments. This is attributed to the physical barrier effect of the hydrophobic coating on moisture, temperature, and acidic and alkaline substances that may cause the collapse of the alginate network. The network structure of uncoated straws will be destroyed, causing excessive swelling of the straws, structural deterioration, and poor consumer experience, further proving the positive role of alcohol-soluble protein coating in improving straw performance.
[0100] In summary, the present invention combines the antisolvent and the electrostatic assembly method, and by adjusting the pH, the zein undergoes a protonation reaction, carries a positive charge, and undergoes electrostatic assembly with the charged alginate on the surface of the straw, thereby achieving a stable interface bond, and the zein coating is added to the surface of the straw. Due to the hydrophobicity of the zein, the straw with the zein coating has excellent water resistance. In addition, the mechanical properties of the seaweed-based straw after the coating are also greatly improved.
[0101] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for improving the performance of seaweed-based straws, characterized in that: The steps include: The seaweed-based straws are immersed in a zein solution for reaction. After the reaction is completed, the straws are taken out, washed, and dried to obtain seaweed-based straws with improved performance and zein coating.
2. The method according to claim 1, characterized in that The reaction time is selected from 1 to 3 hours.
3. The method according to claim 1, characterized in that The zein solution is an alcohol solution of zein; the concentration of the zein solution is selected from 1 to 6%.
4. The method according to claim 3, characterized in that The concentration of the zein solution is 2%.
5. The method according to claim 1, characterized in that The alcohol aqueous solution is composed of ethanol and water, and the volume ratio is selected from 7-9:1-3.
6. The method according to claim 1, characterized in that The pH of the zein solution is selected from 2 to 8.
7. The method according to claim 6, characterized in that The pH of the zein solution is 4.
8. The method according to claim 1, characterized in that The seaweed-based straw is prepared by the following method: (1) Preparation of gel mold Dissolving agar powder and calcium chloride powder in water, stirring and heating; then, pouring the agar solution into a tube mold; solidifying to form a sol-gel transition, and obtaining a gel mold; (2) Cross-linking and demolding Dissolving sodium alginate powder in water to form a sodium alginate solution; then, immersing the gel mold in the sodium alginate solution to perform directional diffusion cross-linking; After the cross-linking is completed, the gel mold is taken out to obtain a hollow tube; the hollow tube is immersed in a calcium chloride solution; Subsequently, the hollow tube is immersed in water to remove excess calcium chloride, thereby obtaining a cross-linked and strengthened hollow tube; The hollow tubes are dried to obtain seaweed-based straws.
9. The method according to claim 8, characterized in that: In the step (1), the mass ratio of agar powder, calcium chloride powder and water is selected from 0.5 to 10:1 to 30:100; and / or, the temperature is heated to 85 to 100° C.; and / or, the curing conditions are selected from: curing at 0 to 50° C. for 5 to 100 min; In the step (2), the concentration of the sodium alginate solution is 0.5 to 15% wt; and / or the immersion time in the sodium alginate solution is 10 to 120 min; and / or the concentration of the calcium chloride solution is selected from 0.1 to 1.5 M; and / or the time in the calcium chloride solution is 5 to 120 min; and / or the time in the water is 5 to 60 min.
10. A seaweed-based straw coated with zein prepared by the method of any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of edible and biodegradable tableware
CN114311721A